Influência de diferentes métodos de restauração ecológica sobre a assembleia de aves em agroecossistema subtropical no Brasil. - Vogel, Huilquer Francisco (2014)
Ecological restoration allows manipulation of the complexity and heterogeneity of the landscape, which are decisive for the structuring of animal communities. In this sense, in the first study, diversity parameters of the bird assemblage were evaluated in experimental plots using three ecological restoration techniques: nucleation (NC), passive restoration (PR) and high diversity planting (HD). We tested the hypothesis that artificial perches used in ecological restoration are crucial for promoting increased richness and diversity of birds in plots restored through nucleation. In addition, we investigated the ability of different restoration techniques to attract birds occurring in nearby forest experiment. In the third chapter, we tested the hypothesis that the structure of the bird assemblage using artificial perches for birds is affected by seasonal variation. Were based on data from 12 experimental plots established in a subtropical agroecosystem being restored in the southwestern state of Paraná, Brazil. Mostly ANOVA was used to compare parameters that make up the diversity. Moreover, the description of the structure and composition of the bird assemblage was done by means of specific tests used in biodiversity studies. In the first chapter, the greatest richness of birds occurs through nucleation (49 ± 2.45 SD species) and the lowest richness occurred in the HD treatment (37 ± 3.14 SD species), with a similar statistical pattern for abundance and diversity (NC > PR > HD). The functional pattern of nucleation shows that the method responds favorably to cases of dynamic equilibrium, heterogeneity and complexity of the landscape. However, when the results obtained solely from artificial perches are disregarded, the pattern of the components of bird?s diversity in the applied nucleation does not differ from that of the passive restoration. High diversity planting had the highest similarity the richness and diversity of avifauna between restoration procedures as regards to the nearby forest, demonstrating that it may have greater medium-term conservation potential. Data from the artificial perches showed that they were ineffective in attracting frugivorous birds, reinforcing that seed dispersal tends to be done primarily by insectivores and generalist omnivores in subtropical agroecosystems, where the richness of the disperser assemblage can be affected by seasonal variation.